Oversharing and its Impact for Children: A Comparative Legal Protection - Sayid Muhammad Rifqi Noval (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
This study aims to identify the potential threat for children resulting from the intense personal data overshare in cyber-space and examine its legal protection. This study uses descriptive qualitative with a case, comparative and conceptual approaches. The primary legal material used in this study is Law No. 44 of 2008 on Pornography (Pornography law) and Law No. 11 of 2008 on Information and Electronic Transaction (ITE law), last amended by law No. 19 of 2016 on the Amendment of Law No. 11 of 2008. The secondary legal material used in this study includes books, journals, and related articles. The result shows that threats resulting from the overshare lead to various offenses like cyberbullying, pedophile threats, identity theft, identity manipulation, deepfake, and cyberstalking. In Indonesia, the legal protection of the children cyber offense victim does not specifically regulate. While learning from several countries, such as the U.S, Canada, France and the U.K, have stipulated the provision regarding children’s protection, especially in cyber-space. Through this study, the author proposed the appropriate regulation to tackle the issues of cyber offense for children in Indonesia by complementing the existing regulation regarding the limitation of oversharing of data in the cyber-space.